La proposta di cooperazione rafforzata sulla legge applicabile a separazione e divorzio: profili problematici - Lopes Pegna, Olivia (CUADERNOS DE DERECHO TRANSNACIONAL, 2010)
On 31 March 2010 the Commission proposed a Council Regulation (UE) implementing enhanced cooperation in the area of the law applicable to divorce and legal separation. On 12 July 2010 the Council adopted a Decision authorising the first enhanced cooperation in the history of the UE. This was first envisaged in the Amsterdam Treaty, and currently in article 20 TEU, and articles 326 ff. TFEU. The proposal basically follows the previous Commission proposal for a Regulation amending Regulation No. 2201/2003 as regards jurisdictional rules and introducing rules concerning applicable law in matrimonial matters (the so-called Rome III Regulation). Enhanced cooperation was authorised by the Council, noting that there were insurmountable difficulties that made unanimity impossible on the earlier proposal. Some new issues arise from the text of the proposal, also as a consequence of the adoption of a regulation, that is separate from the jurisdiction and enforcement Regulation (Brussels II-bis). Among those issues are the scope of the Regulation and the determination of the applicable law. An important concern is ensuring consistency with Regulation No. 2201/2003, and the other regulations on the applicable law, Rome I and Rome II. Several suggestions for amendments to the proposal are made.
Keywords: divorce; conflict of laws; enhanced cooperation; double nationality; lex fori; public policy; non-unified legal systems